Case Studies and Promising Approaches. Vocational Education Equity Study. Final Report Volume III - Wheeler, Jeanette D.; American Institutes for Research in the Behavioral Sciences, Palo Alto, CA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1979)
Information on programs and activities which have been developed to reduce sex inequities in vocational education is provided. The document is organized into two sections: section 1 contains case studies of twelve programs selected from a nationwide search, and section 2 contains brief descriptions of twelve promising approaches to reducing sex inequity, also selected from the nationwide search. Each of the case studies includes the following components: program overview; background and development; program description, target population, staff, facilities, and activities (recruiting, instruction, support services, job development and placement, community involvement, and support); costs and funding sources; program effectiveness; program future; replicating the program; and contact person and program address. Each of the approach descriptions includes the following components: target population, purpose, idea for replication, activities, evaluation and dissemination, funding source, and contact person and address. (JH)
Sponsoring Agency: Office of Education (DHEW), Washington, DC.
Contract Number: 300-77-0318.
ERIC Note: Some of the tables in this document may not reproduce well due to light print; For related documents see CE 022 751-755.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Activities; Case Studies; Information Sources; Program Costs; Program Descriptions; Program Development; Program Effectiveness; Program Evaluation; Sex Discrimination; Sex Fairness; Sex Stereotypes; Vocational Education; Reports, Descriptive; Reports, Research